Micropropagação DE Psidium spp. - Santos, Márcia Adriana Carvalho dos (2015)
Brazil has 47 endemic species of strawberry guava (Psidium spp.), being an important center of genetic diversity of this genus. In the Caatinga biome, the occurrence of the species P. schenckianum Kiaersk, P. guineense Swartz. (most often) and Psidium grandifolium Mart. have been reported. These species have great potential for economic exploitation of the fruit, which is rich in vitamin C and can be consumed fresh or processed in the form of juices, sweets, jams, jellies and ice cream. It also presents outstanding antimicrobial activity, pharmacological and antioxidant as well as essential oils. In addition, strawberry guava are the main sources of resistance to nematode (Meloidogyne enterolobii), which is the main pathogen of guava (P. guajava). This resistance can be transferred to the Paluma guava (cv. GP). However, the strawberry guava is endangered in its natural environment and presents limitations in vegetative propagation by conventional methods, making impossible cloning the resistant plants. Micropropagation is a viable propagation technique of species susceptible to extinction and difficult vegetative propagation. Protocols allowing the cloning of this species for future studies should be improved. Thus, the aim of this research is to develop a protocol for micropropagation of Psidium spp., determining the culture medium, conditions of gas exchange, type of explant and concentration of growth regulators. Seedlings of three access of strawberry guava and cultivar guava paluma (cv.GP) were grown under the following conditions: JADS culture medium, MS and WPM to determine the culture medium; and medium JADS sealed with lids without membrane (SM), one membrane (1M) and two membranes (2M) with carbon dioxide exchange rates (TTCO2) 14; 21 and 25 μL L-1, respectively, to determine the best seedling growth in TTCO2 Psidium spp. After this, different explants of Brazilian guava trees were transferred to regeneration media with different concentrations of indolbutyric acid (IBA): 0, 2.46, 4.92 and 9.84 mM in rooting induction and benzyladenine (BA): 0.0, 2.2 and 4.44 mM; BA + naphthaleneacetic acid (NAA): 2.22 uM BA + 0.054 uM ANA; and 4.44 uM BA + 0.054 uM ANA in regeneration shoots of the following explants: nodal and apical segments in semi-solid culture, stem segments in liquid culture, organogenesis internodal segments, and leaf sections in semi-solid cultureof a P. guineense access and induction of organogenesis in liquid culture using root segments of a P. schenckianum access and three accessions of P. guineense. Seedlings of strawberry guava and cv. GP showed better growth in JADS culture medium. TTCO2 (25 μL L-1) resulted in the growth of seedlings with improved morphophysiological and anatomical characteristics and biosynthesis of compounds of reserve in leaves from both species (P. guineense and P. guajava). This condition is the most indicated for the development in in vitro propagation protocols of Psidium spp. It was not necessary the addition of IBA in the rooting of shoots. Shoots were obtained with and without addition of plant hormones in stem segments, apical segments, nodal and root segments in P. guineense accesses from direct organogenesis, maintaining the same ploidy of the seedlings of this species. In stem segments, the greater number of shoots was observed with 2.22 and 4.44 mM of BA. Shoots were elongated, rooted and acclimatized with 100% survival, showing that the in vitro regeneration protocol established is efficient. This is the first micropropagation protocol established to strawberry guava